Performance of a large reactor in degrading sulfamethazine in water using UV and persulfate. (October 2019) - Lin, Chia-Chang; Wu, Min-Shan
Abstract: This study evaluates the performance of a large reactor in the degradation of sulfamethazine (SMT) in water using UV and persulfate (PS), as well as the effects of UV wavelength, PS concentration, initial SMT concentration, and addition of anions on this process. The degradation efficiency and rate of SMT using the UV-254 nm/PS process were higher than those using the UV-365 nm/PS process. The degradation efficiency of SMT using the UV-254 nm/PS process increased with PS concentration. However, PS at high concentration inhibited the SMT degradation rate using the UV-254 nm/PS process. Reducing the initial SMT concentration increased the degradation efficiency and rate of SMT under UV-254 nm. The SMT degradation using the UV-254 nm/PS process in a large reactor followed pseudo-first-order kinetics. Radical scavenging tests revealed that SO4 − dominated in the SMT degradation using the UV-254 nm/PS process in a large reactor. Adding anions decreased the degradation efficiency and rate of SMT using the UV-254 nm/PS process in the order NO3 −  > SO4 2−  > Cl − . In the UV-254 nm/PS process, SMT (5 mg/L) was completely degraded in 2 min at a PS concentration of 10 mM without the addition of anions. Therefore, a large reactor with high PS concentrations is very effective in degrading SMT in water using the UV-254 nm/PS process.